Assessing the performance of concrete made with recycled latex gloves and silicone catheter using ultrasonic pulse velocity - Al Biajawi, Mohammad I.; Rahimah, Embong; Khairunisa, Muthusamy; Norasyikin, Ismail; Izwan, Johari (Elsevier Ltd, 2023)
Significant advances in concrete technology in modern times have prompted the search for environmentally friendly materials that could improve the properties of concrete. The inclusion of recyclable materials to conventional concrete can help in conserving key resources and produce environmentally friendly concrete. The incorporation of latex gloves and silicone catheter waste in concrete is one of the most important approaches to minimize the environmental problems associated with their disposal. In this study, an experiment was conducted to evaluate the effects of using latex gloves and silicone catheter waste as a substitute for coarse aggregates in concrete mixes. Concrete which was made with latex gloves and silicone catheter waste were subjected to UPV evaluations, i.e., ultrasonic pulse velocity tests at 28 curing days. Compressive strength and workability tests were also performed for reference and compared to the replacement sample. The inclusion of latex gloves and silicone catheter waste in proportions of 2.5%, 5%, 7.5 and 10% decreased the UPV values of the concrete. The results showed that the UPV values of the concrete decreased significantly from excellent to very good to poor for all specimens as the proportion of silicone catheters and latex gloves increased. The results showed that the addition of different proportions of latex gloves and silicone catheters decreased the compressive strength of the concrete by 86% and 59%, respectively, when the proportion of latex gloves and silicone catheters in the concrete mix was replaced by 10%. In addition, the fresh concrete property of concrete containing latex gloves and silicone catheters was decreased by 22% and 53%, respectively, when the proportion of latex gloves and silicone catheters was replaced by 10%. This study helps to raise environmental awareness by improving understanding of the waste generated and the importance of reusing waste as a substitute in concrete mixes.